Peculiarities of introduction of family medicine in Ukraine - Ruslana Slukhenska (Kazimierz Wielki University, 2018)
The introduction of family medicine on the territory of Ukraine now is the subject of many discussions among health system organizers, scientists, teachers, representatives of medical organizations, patient community groups, etc. Aim of the article: to analyze peculiarities of introduction of several stages reform of medical primary assistance of Ukraine. Methods and materials of research: we have applied the methods of comparative analysis, logical generalization, analysis and synthesis for comprehensive estimation of results and peculiarities of introduction of the practice of family medicine. Results: the scientific work analyzes the peculiarities and ways of introducing several stages of the reform of medical primary care of Ukraine as a guarantee of the total change in all levels of medical care and overcoming the health and medical crisis of the country. Conclusions. Introduction of primary link of medical provision of family medicine in Ukraine happens during difficult socially-economic conditions and in realities of non-proclaimed war, that significantly slows down the process of realization. Gradual implementation of economic methods into management of family medicine allows to gain significant progress in increasing quality of medical-sanitary provision of population, strengthen and saving its health, improvement of world rating of Ukraine. It became clear, that the effectiveness of introducing family medicine exceeds the expected results both for citizens and medical institutions and for the state as a whole for a short term of local implementations.